PEMBELAJARAN IPA BERBANTUAN MEDIA AUDIOVISUAL DALAM MENINGKATKAN HASIL BELAJAR SISWA DI MIS AMANAH RUTENG - Yosef Firman Narut; Zephisius R. E. Ntelok (JIPD (Jurnal Inovasi Pendidikan Dasar), 2020)
This study mainly aims to determine the effect of the use of audiovisual media on learning outcomes of fourth grade students at MIS Amanah Ruteng in the 2018/2019 school year. This research includes quantitative research, with the type of experimental research. The design in this study was the prepostest control group design. The sampling technique is done by total sampling, which the entire population of fourth grade is used as a sample. The research sample consisted of 21 students of 4thA grade as the control class and 21 students of 4thB grade as the experimental class. The data collection technique in this study was a multiple choice test technique with 30 instruments. The results of the validity test contained 26 valid items and 4 items were invalid with a reliability of 0.932. Based on the results of the analysis showed the value of tcount was 7.38 and the value of ttable was 2.02 at a significance level of 0.05. The calculation results showed the value of tcount 7.38 > 2.02 ttable. This shows that the null hypothesis (Ho) was rejected and the alternative hypothesis (Ha) was accepted. Based on the results of this study, it was concluded that science learning assisted by audiovisual media was proven to be able to improve student learning outcomes.